Math
posted by Hanu .
simplify using the exponent law. express your answer using positive exponents only.
(x^2)^3(2x^3)^3/(4x)^2

( x ^ 2 ) ^ 3 = x ^ 6
( 2 x ^ 3 ) ^ (  3 ) = 2 ^ (  3 ) * x ^ [ (  3 ) * (  3 ) ] =
2 ^ (  3 ) * x ^ (  9 )
1 / ( 2 ^ 3 * x ^ 9 ) = 1 / 8 x ^ 9
3 /( 4 x )^ 2 = 3 / ( 4 ^ 2 x ^ 2 ) = 1 / 16 x ^ 2
( x ^ 2 )^ 3 ( 2 x ^ 3 )^ 3 / ( 4 x ) ^ 2 =
x ^ 6 * 1 / 8 x ^ 9 * 1 / 16 x ^ 2 =
x ^ 6 / ( 8 x ^ 9 * 16 x ^ 2 ) =
x ^ 6 / ( 128 * x ^ 11 ) =
x ^ 6 / ( 128 * x ^ 6 * x ^ 5 ) =
1 / 128 x ^ 5 
CORRECTION:
( 2 x ^ 3 ) ^ (  3 ) = 2 ^ (  3 ) * x ^ [ 3 * (  3 ) ] =
2 ^ (  3 ) * x ^ (  9 )
1 / ( 2 ^ 3 * x ^ 9 ) = 1 / 8 x ^ 9